Improved performance of carbon‐based supercapacitors with sulfonated poly(ether ether ketone)/poly(vinyl alcohol) composite membranes as separators. Issue 1 (9th October 2018) - Liang, Na; Ji, Yongsheng; Zuo, Danying; Zhang, Hongwei; Xu, Jing
Abstract: Supercapacitors have attracted much interest because of their high power density and long cycling life. However, the porous polypropylene membranes that are widely used as separators in supercapacitors are unfavorable for transporting ions and constructing the interfaces between electrolyte and electrodes due to their hydrophobic property. As a consequence, a crosslinked solid polymer electrolyte membrane and a semi‐interpenetrating polymer network (sIPN) were fabricated from sulfonated poly(ether ether ketone) (SPEEK) and poly(vinyl alcohol) (PVA), which can be used as hydrophilic separators. Their structures were examined using Fourier transform infrared spectroscopy. The electrochemical properties of assembled electrical double‐layer capacitors (EDLCs) were investigated using cyclic voltammetry, galvanostatic charging–discharging and impedance analysis. At a current density of 1 A g −1, a single electrode in the EDLC with the sIPN shows a specific capacitance of 134 F g −1 . As a comparison, a single electrode in the EDLC with a SPEEK membrane demonstrates a specific capacitance of only 121 F g −1 . After 1000 charge–discharge cycles, the specific capacitance retentions of both EDLCs are nearly 100%. These results suggest that the sIPN based on SPEEK and PVA has great potential to serve as a separator in EDLCs. © 2018 Society of Chemical Industry Abstract : A semi‐interpenetrating polymer network based on sulfonated poly(ether ether ketone) (SPEEK) and poly(vinyl alcohol) (PVA) was used as an electrical double‐layer capacitor (EDLC) separator. The specific capacitance of the EDLC was increased by 10.7%.